The Development of Biology Module Based On Stem-CP to Improve Critical Thinking and Self-Regulated Learning - Galuh Paramita; Sutarto Sutarto; Wachju Subchan; Indrawati Indrawati (Green Publisher Indonesia, 2022)
This research aimed at improving critical thinking and SRL (Self Regulated Learning) ability based on STEM-CP (Science, Technology, Engineering Dan Mathematic- Contextual Problem) by using module. This research employed a research and development (R&D) method, which was used as actual proof in improving a learning media of STEM-CP based modul. There were 12 schools, including state or private schools, and 12 biology teachers as need analysis involved in this study. A needs assessment was conducted by using a questionnaire generated in Google form. The result of the needs assessment showed that teachers 70% of stated so far the learning process has not run optimally, the media that has been used so far have not maximized the learning process of 66,6%, and 83.3% of teachers stated that learning had used modules, but 16.6% stated that the learning process had not used modules. The fact is that in learning the teacher has used the module but it has not maximized the learning process. The STEM-CP module is expected to be able to improve students' critical thinking skills and SRL (Self Regulated Learning).